Lineage, arrangement, and death of clonally related motoneurons in chick spinal cord - Leber, SM (J Neurosci, 1990)
We have used recombinant retroviruses as lineage markers to study the genealogy of motoneurons (MNs) in the chick spinal cord. We infected individual progenitors by injecting virions into the neural tube at stages 11–18, a few cell divisions before MNs are born. The descendants of infected cells were subsequently detected with a histochemical stain for beta-galactosidase (lacZ), the product of the retrovirally introduced gene. Clonally related, lacZ-positive cells formed clusters that were usually radial or planar in shape. The cells that comprised these clones were classified by morphology, size, and location. About 15% of the clones in the spinal cord contained MNs, and these were studied further. Multicellular clones that contained only MNs were infrequent. Instead, close relatives of MNs included a variety of other neurons, as well as glia and ependymal cells. Most non-MNs in these clones were found in the ventral and intermediate parts of the spinal cord. Neurons included interneurons and autonomic preganglionic neurons in the column of Terni. Labeled glia were found in both the gray and white matter and included astrocytes and cells tentatively identified as oligodendrocytes. Thus, even shortly before MNs are born, their progenitors are multipotential. Clonally related MNs were not restricted to a single motor pool. Some clones contained MNs in both the medial and lateral parts of the lateral motor column, which are known to innervate distinct groups of limb muscles. Furthermore, some clones contained MNs in the medial motor column (which innervate axial muscles) as well as in the lateral motor column. In contrast, the dispersal of clonally related MNs (and other neurons) was restricted in the rostrocaudal axis; most clones were less than one-quarter segment in length. Thus, MNs derived from a single progenitor are more likely to share rostrocaudal position than synaptic targets. To investigate the fate of clonally related MNs, we counted the number of MNs per clone at times before, during, and after the major period of MN death. The number of MNs per clone declined in precise parallel with the total number of MNs during this period, suggesting that neurons are eliminated without regard to their clone of origin. This result implies that the decision to live or die occurs on a cell-by-cell rather than a clone-by-clone basis.